The Campus Canopy, 1940-01-12 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1940)
The Campus Canopy, January 12, 1940. Vol. 6, No. 9. -- Philharmonic Will Bring Symphony -- Reade Announces Regulations For Use Of Music Set -- 33 Students Make Dean’s List -- Callaway And Forsythe Switch Home Ec. Posts -- Gulliver Speaks To Fine Arts Club -- Within 3 Days Within 3 Days -- New Orleans Is Chosen As Site Of Senior Trip -- Co-op Store Voted One Of Best Enterprises Of Year -- Enrollment Includes 13 New Students -- Girls Sleeping In Class Hear New Alarm Clock
## Campus Canopy Staff: Louise Bell (Editor); Linda Summer (Managing Editor); Rosemary Baker (Assistant Editor); Curtis Whatley (Business Manager); Alice Wlsenbaker (News Editor); Susie McKey (Feature Editor); Harriet Flournoy (Sports Editor); Gwendolyn Hendricks (Headline Writer); Runnelle Prance (Exchange Manager); Inez Taylor (Circulation Manager); (Reporters:) Jane Ellen Smith, Betty Williams, Rosemary Stein, Jeanne Pryor, Kitty Davis, Carolyn Stump. Ruth Dixon, Frances Kennedy, Betty Franklin, Jacqueline Smith, Annabels Sherman, Doris Land, Louise James, Barbara Landstreet, Sara Wade. Doris Hiers, Eunice Fairchild, Wilma Cody, Mary Newton, Leonora Peeples, Betty Barnes, and Kathryn Abell. (Proofreaders:) Edith Wilson, Evelyn Woodward, Ruth Sessoms, Louise Lambert. (Advertising Staff:) Jacqueline Abrahams, Carolyn Bridges, Evelyn Brim, Mary Alice Brim, Mary Dell Drenon, Eunice Fairchild, Doris Hiers, Margaret Hiers, Doris Kent, Mary Lanier, Alice Meadors, Harriet Miller, Ellen Mobley, Eleanor Morgan, Mary North, Virginia Parrish, Vivian Reed, Beth Rollison, Ruth Sessoms, Sunshine Taylor, Susanne Wanna- maker, Della Wentz. ## NAMES: Aileen Bartlett; Alice Meadors; Alice Wisenbaker; Anabel Sherman; Anne Eager; Anne Holloway; Anne Parham; Annie B. Croft; Annie P. Hopper; Aubrey Williams; Bara Garbutt; Barbara Landstreet; Beth Rollison; Bette Davies; Betty Barnes; Betty Boop; Betty Franklin; Betty Williams; Beverly Dougherty; Bill Mac; Billie Green; Bob Belcher; Buddy Wirick; Carolyn Marshall; Carolyn Stump; Cary Grant; Catherine Young Graham; Chopin; Christine Poss; Clark Gable; Claudette Colbert; Corinne Smith; Curtis Whatley; David Lipscomb; David Niven; Deanna Durbin; Della Wentz; Doris Harper; Doris Hiers; Doris Kent; Doris Land; Dorothy Mitchell ; Douglas Fairbanks; Edith Wilson; Edward G. Robinson; Edward Grieg; Eleanor Cook; Eleanor Morgan; Elizabeth Fender; Ella Sue Traynham; Ellen Smith; Emil Borte; Emily Garner; Errol Flynn; Eugenia Shaw; Evelyn Brim; Evelyn Woodward; Frances Davies; Frances Kennedy; Frances Middleton; Frank R. Reade; Fred MacMurray; Geraldine Bowen; Gloria Dalton; Gloria Gilder; Grace Williams; Greta Garbo; Gwen Winters; Gwendolyn Hendricks; Harold Gulliver; Harriet Flournoy; Harriet Good; Harriet Miller; Hattilu McIntyre; Hedy Lamarr; Helen Duncan; Helen Parrish; Helen Quarterman; Helen Rountree; Hilda Sikes; Inez Taylor; Irwin Smith; Ivelyn Folsom; Jacqueline Abrahams; Jacqueline Smith; James Stewart; Jane Ellen Smith; Jane Gates McKey; Jane McKey; Janie Rae White; Jean Burns; Jeanne Pryor; Jenelle Miley; Joan Bennett; Joe Schmidt; John C. Baker; John Campbell; John Steinbeck; Johnny Johnson; Josephine Graham; Kathryn II; Kathryn Scott; Kitty Davis; Leecy Ann Goodloe; Leonora Peeples; Lew Ayres; Linda Darnell; Linda Summer; Little Willie; Lois Christian; Louise Bell; Louise Blanks; Louise James; Louise Lambert; Mabel Peterson Godwin; Madeline Carroll; Margaret Burns; Margaret Copeland; Margaret Dutton; Margaret Earle McRae; Margaret Hiers; Margaret Sullivan; Margaret Wood; Marguerite Norton; Marie Ambos; Marion Git; Marnclle Parker; Martha Wilkes; Mary Alice Brim; Mary Catherine Abernathy; Mary Dell Drenon; Mary Elizabeth Johnson; Mary Jane Bixler; Mary Jean Rockwell; Mary Josephine Ford; Mary Lanier; Mary Martha Watson; Mary McCoy; Mary Newton; Mary North; Mary Virginia Lord; Matilda Callaway; Maxwell Williams; Melvyn Douglas; Mickey Rooney; Mildred Fisher; Mildred Teasley; Mildred Wilson; Minnie Mouse; Minnie Roberts; Montine Cowart; Myrna Loy; Ora Kate Wisenbaker; Pat Parrish; Pattye Patterson; Paul Muni; Paul S. Havens; Popeye; Porky Pig; Priscilla Lane; R. DeWitt Brown; Ray Kleve; Ray Milland; Rhett Butler; Rosalind Russell; Rosalind Taylor; Rose Frances McLeod; Rosemary Baker; Rosemary Bowden; Rosemary Stein; Rudolf Frimal; Ruth Dixon; Ruth Morgan; Ruth Reid; Ruth Sessoms; Ruth Whisonant; Saint Saens; Santa Claus; Sara Katherine ; Sara Wade; Sigmund Romberg; Sis Williams; Sonja Henie; Spencer Tracy; Star Clark; Sunshine Taylor; Susanne Wan; Susie McKey; Suzanne Wannamaker; Tahaikowsky; Thelma Sirmons; Tom Fischer; Virginia Marion Chambers; Virginia Zachert; Viva McGeachy; Vivian Reed; Von Suppe; Wilma Cody; ## Locations: Acworth; Alabama; America; Atlanta; Bennington; Big City; Boston; Branford; California; Columbus; England; Florida; France; Georgia; Hahira; Hawkinsville; House-in-the-Woods; Iowa; Jacksonville; Los Angeles City College; Macon; Madison Ave. New York; Mardi Gras; Miami; Minneapolis; Missouri-Kansas; New Orleans; New York; North Florida; Oklahoma; Palestine; Paris; Roosevelt Hotel; Savannah; Scandinavia; South Carolina; Southwest; Tennille; Texas; United States; Valdosta; Winston-Salem; ## Organizations: Bessie Tift College; Camera Club; Campbells; Chemistry Division; Clark University; Clemson College; Clemson; Collegiate Digest; Cornell University; Drake University radio; East Texas State Techers College; English Club; Eunice Fairchild; Fine Arts Club; Foreign Legion; General Merchandise Store; Georgia State Womans College; Harvard; Home Economics; Indiana University; Massachusetts State College; National Student Federation; Ohio State University; Peabody College; Philharmonic Club; Post Office; South Georgia College; Sports Club; Stationery Company; Texas Tech; The Bradley College; The University of Florida Symphony; University of Cincinnati; University of Florida Symphony Orchestra; University of Kansas; University of Minnesota; University of Tennessee; Valdosta State University Archives; Virginia Power; Wilson College; Woman’s College of the Ball; Digitized from original print, Valdosta State University Archives and Special Collections, January 6, 2016.
Keywords: The Campus Canopy; 1940s; 1940; The Georgia State Woman's College; GSWC; Valdosta State College; VSC; Valdosta State University; VSU